Adult Vocational Training and Government Policy in France and Britain. - Greenhalgh, C (1999)
Provision of continuing vocational training is subject to several market failures: capital-market imperfections (credit constraints), risk arising from variability of future values of skills, mismatch of costs and returns owing to worker mobility, and general positive externalities of human capital. In the light of these market imperfections we evaluate the contrasting French and British systems of adult training. French policy is interventionist and includes an employer training levy. British policy has abandoned levies and emphasizes individual initiatives by workers and employers. Despite contrasting policies, the character of training provision is similar in both countries, being mainly arranged and financed by employers. Differences are that the French system offers both higher public subsidy and cost-sharing between training and non-training employers. Training provision is higher in France and occurs earlier in the working life-cycle. We conclude British policy could usefully reconsider employer levies for solving training under-investment.